Overconfidence and entrepreneurship: A meta-analysis of different types of overconfidence in the entrepreneurial process - Kraft, Priscilla S.; Günther, Christina; Kammerlander, Nadine H.; Lampe, Jan (Journal of Business Venturing, 2022)
While research on overconfidence and entrepreneurship has grown rapidly in recent decades, extant studies provide conflicting theoretical predictions and empirical results about the role of overconfidence for entrepreneurship. To help resolve the controversy in the literature, we draw on information-processing theory to propose a theoretical framework that disentangles the influence of three types of overconfidence (i.e., overprecision, overestimation, and overplacement) in three major phases of the entrepreneurial process. The results of meta-analytical structural equation modeling (MASEM) based on 62 primary studies reveal varying effects of the three types of overconfidence in the entrepreneurial process. We discuss the implications of these findings and identify future research opportunities to advance this stream of research.